WATER RELATION FEATURES OF NERIUM OLEANDER L. UNDER PROGRESSIVE SOIL DROUGHT STRESS - Svetlana P. Korsakova; Yuriy V. Plugatar; Oleg A. Ilnitsky; Emil I. Kleiman (Юг России: экология, развитие, 2018)
Abstract. Aim. Study the ecophysiological reaction of Nerium oleander L. on effect of progressive soil drought. Estimate the optimal and threshold values of environmental factors limiting photosynthesis rate of Nerium oleander L. plants. Materials and Methods. As the research materials, were used the young plants of Nerium oleander L. For continuous automatic recording of CO2/H2O gas exchange of intact leaves we used PTM-48A Photosynthesis Monitor. Results. It was established that N.oleander begins sense a water stress deficit during the critical period of active growth by reducing soil moisture content up to 35% field capacity (FC). Net photosynthesis (PN) and stomata conductance (gs) decreased under progressive soil drought stress and dropped to zero under condition: soil water beneath 2-4%VWC (6-11% FC) during more than 24 hours, leaves temperature – more than 37°C and PAR – more than 1300-1700 µmol/(m2 s). Optimal light and temperature conditions for intensive growth: leaf temperature from 23 to 36.5°C, light regime: full sunlight in the range PAR 850-1600 µmol/(m2 s) when soil moisture 45-75% FC. Conclusion. Genotypic characteristics of N. oleander plants in supporting optimal on accordance with the environmental conditions water balance were determined. One of the specific adaptation reaction for N. oleander to extreme drought conditions in case of complex influence of water stress (soil water content at level of wilting range (<6% FC) during more than 48 hours), high levels of irradiance and overheating is the accelerated senescence and exfoliation not only old but also young leaves resulting in the loss of ornamental value cultivar.